The Effect of Marketing on Consumer Loyalty to the Cosmetic Business Beautyessence with Customer Satisfaction as an Intervening Variable - Kurniawati, Syela; Kodrat, David Sukardi (KnE Social Sciences, 2021)
This research was conducted with the aim of analyzing the influence of marketing mix on consumer loyalty to the cosmetic business Beautyessence with consumer satisfaction as an intervening variable. The variables examined were the marketing mix (X), consumer satisfaction (Y1) and consumer loyalty (Y2). The indicators used for the marketing mix were the product, price, place and promotion. Data were analyzed using the Structural Equation Model (SEM). The sample of 97 respondents were Beautyessence consumers who had made purchases a minimum of 2 times; they were recruited using simple random sampling. The marketing mix had a significant positive effect on consumer satisfaction and consumer loyalty; consumer satisfaction had a significant positive effect on consumer loyalty; and marketing mix had a significant effect on consumer loyalty with consumer satisfaction as an intervening variable with a mediation effect of 30.7%. Keywords: marketing mix, consumer satisfaction, consumer loyalty, SEM